The complete mitochondrial DNA of Gymnocypris potanini firmispinatus and comparative mitogenomic analyses of the Gymnocypris species. Issue 1 (1st January 2016) - Hu, Jiaxiang; Cai, Yueping; Xiong, Sen; He, Zhide; Li, Song; Wang, Xiongyan; He, Zhi; Yan, Taiming
Abstract: The complete mitochondrial genome of Gymnocypris potanini firmispinatus was sequenced and compared with others Gymnocypris species. The mitochondrial genome, consisting of 16, 680 base pairs (bp), encoded 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs and a non-coding control region, as those found in other Gymnocypris species. These results can provide useful data for further studies on taxonomic status, molecular systematics and stock evaluation.